Das ERP-Betriebsdatenarchiv als Eine Grundlage für Empirische Controlling-Forschungen - Kluge, Paul-Dieter (ERP systems – database of enterprise as the base for empirical controlling research, 2008)
The application of standard software in an enterprise leads to the possibility of the use of electronic database archives in small businesses. This paper presents the example of ERP software and discusses to what extent the database archive may be used as an empirical basis for controlling. Moreover it presents the weakness of traditional controlling tools, that relates to an empirical proof.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 172-180